Trimetazidine for prevention of induced ischemia and reperfusion of guinea pig retina - Demir, T.; Turgut, B.; Ozercan, I.; Gul, F. C.; Ilhan, N.; Celiker, U. (Dove Medical Press Ltd, 2010)
Objective: Trimetazidine (TMZ) has been used to protect against ischemia/reperfusion (I/R) injury of many tissues. We aimed to evaluate the effect of TMZ during retinal I/R in a guinea pig model. Study design/patients and methods: An experimental study in retinal I/R. Three groups of five guinea pigs were studied to include a control, placebo, and drug test groups. Prior to the application of 90 minutes of high intraocular pressure (IOP) to induce retinal ischemia followed by 24 hours of reperfusion, we applied intraperitoneal saline to the placebo group and 3 mg/kg of TMZ for the drug test group and repeated the injections at intervals of six hours for four cycles. Both eyes of the animals were enucleated at the end of the reperfusion period. Biochemical assay and histopathologic evaluation was performed on one randomly selected eye of each animal. The level of retinal-free malondialdehyde (MDA) and retinal layer thicknesses were determined and comparisons were then made with the control group. Results: The mean free MDA level increased in the placebo group (P = 0.006) but not in the drug group (P>0.05). We observed polymorphonucleated leukocyte infiltration, retinal edema and hydropic degeneration in the retina of the placebo group. However, significant histopathologic change was not observed in specimens of the drug group. Conclusions: This study suggests TMZ has a beneficial effect on retinal lipid peroxidation and histopathologic changes due to I/R injury.
Keywords: ischemia/reperfusion; retina; trimetazidine